REMOTE ESTIMATION OF TOTAL SUSPENDED SOLID (TSS) TRANSPORT AFFECTED BY TIDAL BORE âBONOâ OF KAMPAR BIG RIVER ESTUARY USING LANDSAT 8 OLI IMAGERY - Wisha, Ulung Jantama; Dhiauddin, Ruzana; Kusumah, Gunardi (Marine Research in Indonesia, 2017)
The Kampar River estuary has a unique tidal bore, namely Bono. A tidal bore is a natural phenomenon caused by the tidal flow which meet the flow of the river. Tidal bore "Bono" has an impact on the transport of suspended particles which is pretty much along the Kampar River. The purpose of this study is to determine the estimated concentration of total suspended solid in the river as the result of the transport by Bono in Kampar River estuary by Landsat 8 OLI. The primary data are Landsat 8 OLI sensor â on Path 126 and Row 60, recording date was on 23 -04-2016, which was analyzed spatially â and TSS in situ. The secondary data are tide forecasting data and topographical map of Indonesia. Distribution of total suspended solid indicates sediment transport and its distribution by TSS values ranged between 10-150 mg.L-1 and TSS in situ value ranged between 42-241 mg.L-1. Tidal range ranged from 0.78 to 4.2 m and current velocity ranged from 0-0.9 m.s-1, which generate tidal bore extending from the mouth to the river body, resulting in suspended particle transport along the river. TSS concentration is higher in the river estuary.